Ocean awareness campaign for environmental well-being in the Upin and Ipin animated series season 11: explore the ocean - Siti Aisyah Yap Abdullah
The world’s ocean covers 71% of Earth’s surface and is an integral part of the environment entrusted to humanity for its care. In this regard, one’s relationship with mother nature is to fulfill their life’s purpose in creating mutual harmony and balance among nature and all beings. At present, there have been significant destruction and damage upon the ocean and marine life caused by humans, thus affecting members of the community whose livelihood depend on it. Multitudes of media platforms currently provide channels to educate the public on the importance of the ocean ecosystem for future generations. Therefore, awareness campaigns on the said ocean conservation through media and communication are imperative to influence attitude and behaviours particularly among young audiences and motivate them to engage and participate in the discourse. This study explores the strategy behind the popular children’s animated series, Upin and Ipin in the introduction of ocean elements to inculcate appreciation for the environment. Using a qualitative content analysis, the animation series was analysed thematically and guided by the Nurul Akma Osman animation publishing model. The findings established that an awareness campaign on environmental conversation is present through the theme elements and topics, plots and scripts, characters and characteristics, and backgrounds that are features of animated series. The presentation based on these elements also reflects the efforts of the animated series to create a more organic approach on greater understanding of mother nature for young children.